(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the accuracy of Xpert MTB/XDR regarding detection for drug resistance of INH, FLQ and injectable drugs. Methods: 100 RR-TB patients were tested for drug resistance detection by Xpert MTB/XDR test, MTB firstline, secondline LPA test and phenotypic drug susceptibility testing, a cross-sectional study. Results: The sensitivity of Xpert MTB/XDR testing regarding drug resistance detection was 98.85% for INH, 80% for FLQ, 83.33% for AMK, 100% for KAN and CAP. The specificity for all drugs resistance detection achieved 95%-100%. Positive Prediction Value (PPV) ranged among 94-100%, except KAN’s with 85.71% and CAP’s with 33.33%. Negative Prediction Value (NPV) for all drugs obtained 92%-100%. Concordance based on Cohen’s kappa value between Xpert MTB/XDR and MTB firstline, secondline LPA ranged 0.9-1.0 regarding INH/ FLQ resistance detection, 0.6-0.7 for AMK, KAN and CAP resistance detection. Conclusion: Xpert MTB/XDR testing had high sensitivity and specificity in INH, FLQ, and injectable drugs resistance detection as well as obtained high concordance when compared with MTB firstline, secondline LPA. Xpert MTB/XDR testing is considered as a rapid, simple molecular drug resistance test which would be an effective diagnosis tool for Vietnam National TB Control Program to improve the coverage of diagnostic tests for detection of drug resistance in the upcoming time.